The selective separation of thorium from uranyl ions using ultrasonic-assisted solidified floating organic drop microextraction. Issue 6 (25th May 2021) - El-Gamal, Ghada G.; Mortada, Wael I.; Hassanien, Mohamed M.; Ibrahim, Amr A.; Abou El-Reash, Yasmeen G.
Abstract : The selective separation of thorium via ultrasonic-assisted solidified floated organic drop microextraction using morin as a complexing agent is reported. Abstract : The accurate determination of thorium (Th 4+ ) in the presence of uranyl ions (UO2 2+ ) is a challenge facing analytical chemists. In this article, a solidified floating organic drop microextraction procedure (SFODME) combined with inductively coupled plasma-optical emission spectrometry (ICP-OES) is presented for the separation of Th 4+ from UO2 2+ . Morin (2′, 3, 4′, 5, 7-pentahydroxyflavone) selectively forms a stable complex with Th 4+ in an acidic medium (pH 2.5), while UO2 2+ does not. The formed complex can be separated into an organic drop of 1-undecanol in the presence of ethanol as a dispersive solvent. The major factors influencing the achievement of SFODME, that is, pH, morin concentration, the type and volume of the extracting and dispersive solvents, the sonication conditions, the ionic strength, and the presence of foreign ions, were investigated. Under optimum conditions, the calibration graph was linear in the range of 0.3–400.0 μg L −1 . The detection limit and enrichment factor values were 0.12 μg L −1 and 31.1, respectively. The relative standard deviation for 12 replicates was 1.5%. No significant effects from potentially interfering species, including f-block elements, were observed. The procedure was effectively applied for the determination of Th 4+ in phosphate rock and ceramic tile samples.